Bathroom contamination by antibiotic-resistant Enterobacterales (ESBLPE and CPE): an experimental study. Issue 2 (October 2020) - Sevin, T.; Goldstein, V.; Lolom, I.; Lenne, F.; Gaudonnet, Y.; Baptiste, A.L.; Bendjelloul, G.; Armand-Lefevre, L.; Lucet, J.C.
Summary: Background: Extended-spectrum β-lactamase-producing Enterobacterales (ESBLPE) and carbapenemase-producing Enterobacterales (CPE) cause serious infections. Their presence in urine may lead to environmental contamination potentially responsible for cross-transmission. Aim: To evaluate the level of spraying and contamination after emptying urine in the toilet and rinsing in the sink, a common practice in the healthcare setting. Methods: For each test, the procedure was similar: seat raised, emptying urinal bottle into the toilet at the height of the bowl, rinsing in the sink and flushing. To study splash-drops, water and fluorescein were mixed in the urinal bottle. In each area, the splash-drops frequency and level were assessed with UV. To study contamination, three ESBLPE and one CPE were diluted in saline, 10 6 /mL. Contamination was assessed by sampling before, immediately after and 3 h after the test. The swabs were cultured and the colonies counted and identified. Findings: The areas at the highest risk of spraying were the toilet bowl contour ( N = 36/36), the underside of the toilet seat ( N = 34) and the inside of the sink ( N = 34). Except for gloves ( N = 14), there was low clothing contamination. The most frequently contaminated areas were inside the sink (40/48), where the highest levels of contamination were found (14/48). Conclusion: Emptying the urinal bottles in the toilet followed by sink rinsing is associated with a significant risk of projection and contamination, depending on the area (highest risk at the sink), but the bacteria did not survive beyond 3 h. This practice, which carries a risk of cross-transmission, should be reviewed.